Los Scolytidae de Costa Rica: clave de géneros y de la subfamilia Hylesinae (Coleoptera) - Wood, Stephen L (Universidad de Costa Rica, 1991)
This paper is part of a monograph on the taxonomic determination of Scolytidae species reported from Costa Rica or potentially present in the country. The next two parts will appear in issues 2 and 3 (volume 39) of this journal. This part ¡neludes a key to all genera as well as the species of the genera Bothrosternus, Cnesinus, Chramesus, Eupagiocerus. Phloeoborus. Phloeotribus. Phrixosoma. Sternobothrus, y Xylechinus. and a key to species of Hylesine. For each species, detailed locality and host data are included. Both keys are not useful for specimens collected outside Costa Rica.